Symmetry of upper eyelid after unilateral blepharoptosis repair with minimally invasive conjoint fascial sheath suspension technique - Yianzhu Liu; Wenli Chen; Xia Chen (International Journal of Ophthalmology, 2024)
AIM: To investigate the symmetry of upper eyelid in patients with unilateral mild and moderate blepharoptosis who underwent unilateral minimally invasive combined fascia sheath (CFS) suspension. METHODS: A retrospective study of patients who underwent unilateral minimally invasive CFS suspension surgery between January 2018 and December 2021. Inclusion criteria included unilateral mild and moderate ptosis, good levator muscle function (>9 mm) and follow-up of at least 6mo. Pre- and post-operative symmetry was graded subjectively for marginal reflex distance 1 (MRD1), tarsal platform show (TPS) and eyebrow fat span (BFS). A t-test was used to evaluate MRD1, TPS and BFS asymmetry by calculating delta values. The Bézier curve tool of the Image J software was used to extract the upper eyelid contours, where the symmetry was measured by the percentage of overlapping curvatures (POC). RESULTS: Totally 105 patients (105 eyelids) were included (mild group, n=84; moderate group, n=21). Postoperatively, all patients increased MRD1 and decreased TPS in the ptotic eye while maintaining unchanged BFS. The asymmetric delta value for MRD1 was measured to be 1.48±0.86 preoperatively, and it decreased to 0.58±0.67 postoperatively in all cases (P=0.0004). In patients with mild ptosis, the asymmetry value of TPS fell significantly from 1.15±0.62 to 0.68±0.38 (P=0.0187). The symmetry of the upper eyelid contour increased in all subgroups of patients, with a POC of 59.39%±13.45% preoperatively and POC of 78.29%±13.80% postoperatively. CONCLUSION: Minimally invasive CFS suspension is proved to be an effective means of improving the symmetry of unilateral ptosis in terms of MRD1 (all subgroups), POC (all subgroups) and TPS (only mild group), whereas BFS is unaffected.